Evaluation of microorganisms isolated from blood cultures and their susceptibility profiles to antibiotics in five years period - Arabacı, Çiğdem; Kutlu, Orkide (Journal of Surgery and Medicine, 2019)
Aim: In starting antibiotic treatment to know the distribution of infectious agents and the antibiotic resistance rates is vital especially in critically ill patients to prevent disease progression. In this study we aimed to determine the distribution and antimicrobial resistance patterns of blood culture isolates obtained in a tertiary center. Methods: The microbiological laboratory records between January 2014 and December 2018 were retrospectively reviewed. Each conventional aerobic blood culture bottle per patient with positive results was recorded with the antimicrobial susceptibility profiles of the bacteria isolated. Descriptive statistics (number, percentage, mean and median) were performed. Comparison of descriptive data between groups was performed with cross tables and chi square test. One-way ANOVA test was used to compare the antibiotic resistance rates between spp. Results: A total of 66004 blood cultures were analyzed in this cross-sectional study. Of the 3882 (21.0%) positive results, 3256 (4.9%) were identified as contamination. The most commonly isolated microorganisms were Coagulase negative staphylococcus, Escherichia coli, Klebsiella spp., Staphylococcus aureus and Acinetobacter spp. Extended spectrum β-lactamase (ESBL) positivity was determined in 236 (62.4%) isolates of E.coli, and 186 (56.8%) isolates of Klebsiella spp. Vancomycin resistance showed a significant increase in Enterococcus spp. in time. E.coli did not show any resistance to imipenem, meropenem, tigecycline or colistin. Methicillin susceptible Staphylococcus aureus (MSSA) and methicillin resistant Staphylococcus aureus (MRSA) did not show any resistance to vancomycin, teicoplanin, linezolid or daptomycin. In Enterococcus spp., tigecycline resistance was 1.9%, while daptomycin and linezolid resistance were not determined. The most effective resistance agent to Acinetobacter spp. and Pseudomonas spp. was colistin. Fungal infection was detected in 156 patients. Candida albicans and Candida parapsilosis complex were the most common isolates. Conclusion: Antibiotic resistance rates are increasing in all over the world. Rational antibiotic usage may aid the clinicians to overcome this condition. Epidemiological data is important in this regard.